Karakteristik Model Pendidikan Islam Nusantara: Integrasi Nilai Islam dan Budaya Lokal dalam Pembentukan Pendidikan Holistik - Irbab Aulia Amri; Akhsanul Husna; Ali Imron (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Islamic education in the Indonesian archipelago is a model of education unique to Indonesia that combines Islamic teachings with local cultural values. This model developed through a peaceful and cultural process of Islamization, particularly through Islamic boarding schools and religious teachers. This article discusses the characteristics of Islamic education in the Indonesian archipelago from six main aspects: philosophy, educators, students, material, educational tools, and environment. Islamic Education in the Archipelago emphasizes not only cognitive aspects, but also the moral, spiritual, and social aspects of students. In the context of modern challenges, this model demonstrates its relevance as an inclusive, moderate education system with strong cultural roots. This study shows that Islamic Education in the Archipelago has made a significant contribution to the development of national education with character.